Lower financial literacy induces use of informal loans - Santos, Danilo Braun (2018)
Finance literature documents associations between a family’s financial literacy and its propensity to borrow. However, most studies focus exclusively on formal loan markets. Based on 2,023 observations about financial behavior of Brazilian families, we examined the impacts of financial literacy on informal borrowing, such as loans from friends or moneylenders. Using multinomial logit models, we compared financial literacy’s effects on the propensity to take informal loans between families that did not borrow at all and those who took bank loans. Financial literacy is measured by the investment in capitalization bonds, a financial instrument in the Brazilian market. The results suggest that financial literacy’s relevance to informal loans may exceed that for formal credit channels.